Systemic Barriers to French Immersion in New Brunswick - Julianne Gerbrandt (Canadian Society for Studies in Education, 2022)
French Immersion is a popular program in New Brunswick; however, a growing body of research warns that it might contribute to inequities in public education. This analysis of a typical New Brunswick grade three FI literacy block draws from Bourdieu and Passeron's (1977) theory of social reproduction to identify and explain the persistence of systemic barriers to the program. By relating the concept of habitus to the FI classroom, we can identify how cultural capital manifests in FI students. In this way, we can begin to recognize the underlying social forces that predetermine one's likelihood of access and academic success in the popular program.